Effectiveness of Laboratory Management in Efforts to Improve the Quality of Practical Work in the Food Processing Laboratory - Santoso, Minnar Titis; Setyowati, Sri; Hariyati, Nunuk (JMSP (Jurnal Manajemen dan Supervisi Pendidikan), 2024)
Abstract: This study aims to describe and analyze the laboratory management in food management laboratories and evaluate the supporting and inhibiting factors in laboratory management that affect the quality of practical sessions. The research uses a qualitative descriptive method. The results show that the management of food management laboratories includes planning, organizing, implementation, supervision, and evaluation. Supporting and inhibiting factors affecting the quality of practical sessions are analyzed based on aspects of planning, implementation, practical session evaluation, laboratory human resources, facilities and infrastructure, as well as the timing of practical activities. In conclusion, the application of laboratory management functions in food management laboratories is generally effective, although some challenges remain. Supporting factors for practical session quality include well-prepared practical session planning, the presence of lecturers and laboratory assistants during practical sessions, student participation in maintaining laboratory cleanliness, competent teaching staff, availability of facilities and infrastructure, and sufficient time for practical activities. Inhibiting factors include the absence of practical session guidelines, limited practical session time, suboptimal human resource ratios, and the need for improvements in both the quality and quantity of laboratory facilities and infrastructure. Keywords: Laboratory Management, Culinary Arts, Quality of Practicum